2023
DOI: 10.5334/tohm.747
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Ataxias: Primary and Secondary Etiologies, Treatment, and Classification Approaches

Abstract: Background: Episodic ataxia (EA), characterized by recurrent attacks of cerebellar dysfunc tion, is the manifestation of a group of rare autosomal dominant inherited disorders. EA1 and EA2 are most frequently encountered, caused by mutations in KCNA1 and CACNA1A. EA3-8 are reported in rare families. Advances in genetic testing have broadened the KCNA1 and CACNA1A phenotypes, and detected EA as an unusual presentation of several other genetic disorders. Additionally, there are various secondary causes of EA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 157 publications
0
14
0
1
Order By: Relevance
“…84 Acetazolamide and 4-aminopyridine (4-AP) have both been shown in randomised placebo-controlled trials to similarly reduce the frequency of attacks in EA2. 76,85 In comparison, initial observations in patients with SCA27B suggested that 4-AP, but not acetazolamide, may reduce the severity and frequency of ataxic symptoms. 21 These initial findings were largely confirmed in subsequent open-label series.…”
Section: Prospective Treatment Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…84 Acetazolamide and 4-aminopyridine (4-AP) have both been shown in randomised placebo-controlled trials to similarly reduce the frequency of attacks in EA2. 76,85 In comparison, initial observations in patients with SCA27B suggested that 4-AP, but not acetazolamide, may reduce the severity and frequency of ataxic symptoms. 21 These initial findings were largely confirmed in subsequent open-label series.…”
Section: Prospective Treatment Strategiesmentioning
confidence: 99%
“…71,72,75 Acetazolamide also appears to be more effective in EA2 than in SCA27B to decrease the frequency and severity of episodes of ataxia. 51,76…”
Section: Differential Diagnosis Of Sca27bmentioning
confidence: 99%
See 1 more Smart Citation
“…Behandlungsoptionen umfassen systematisches Absetzen des Medikaments in Verbindung mit Zykloplegie, antiglaukomatösen Medikamenten und/oder Kortikosteroiden. Eine vollständige Auflösung tritt in etwa 5 Tagen ein (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Aufgrund der weit verbreiteten Anwendung von Acetazolamid ist das Wissen über diese idiosynkratische Reaktion entscheidend, um Komplikationen eines Winkelblockglaukoms zu vermeiden.…”
Section: Therapy and Outcomeunclassified
“…Treatment options include systematic drug withdrawal associated with cycloplegia, anti-glaucomatous agents, and/or corticosteroids. Full recovery is achieved within about 5 days (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Given the widespread use of acetazolamide, awareness of this idiosyncratic reaction is crucial to avoid complications of acute angle-closure glaucoma.…”
mentioning
confidence: 99%